Fabius Planciades Fulgentius’ Expositio sermonum antiquorum and its relationship with the Alfonso Fernández de Palencia’s Universal Vocabulario (1490) (Minerva, 2021)
Universal Vocabulario (1490), by Alfonso de Palencia, is still a great unknown despite its being one of the most important works on Spanish lexicography. Not only is the first one to include Spanish, but it is also important for its linguistic and cultural richness. Its author’s humanistic knowledge is manifest in the quantity of classic examples collected and in the treatment of the sources. To those sources already known (Nonous Marcellus, Festus and Papias), the paper intends to add another one, Expositio sermonum antiquorum ad Grammaticum Calcidium by Fabius Planciades Fulgentius.
Keywords: Universal Vocabulario; Alfonso de Palencia; Late Latin Vocabulary; Fulgentius; Medieval Lexicography